Supply chain model for gas pipeline - Yahyazadeh, A. (Asian Research Publishing Network, 2016)
Gas pipeline networks are widely used for gas transportation from gas sources to consumers. The main problem into the gas transfer is to accurately estimate the cost of transportation from production sites to the consumers. From the review of literatures is noted that the computation for optimization of the gas piping did not take into account the gas capacity allocated to each source, processing unit and distribution unit. Also the productive capacities of the different units are considered having the same and constant supply. The main objective of the study is to propose a linear integer programming model for gas distribution network from production sites to consumers for attainment the minimum cost of gas transportation. Incorporating variable capacity and supply of the units. Integer programming adopt the Zero-One approach for solving the model. This model simplify the analysis. The model was applied for analysis of north of Iran's gas. The result reveals that cost of transportation could be reduced approximately by 23 per cent of the transportation cost in comparison to current cost. Â© 2006-2016 Asian Research Publishing Network (ARPN).